Learning English Through Cable News Network Channels: A Focus on Speaking in The Listening for Information and Leisure Course - Hertiwi, Yuni; Djalil, Mashuri; Sadilia, Sukmawati; Marhum, Mochtar (Universitas Pahlawan Tuanku Tambusai, 2026)
This study investigates students’ perceptions of using CNN news videos to support speaking development in a Listening for Information and Leisure course. Many EFL students experience difficulty improving speaking skills due to limited authentic exposure and listening instruction that emphasizes comprehension rather than production. This research employed a convergent parallel mixed-method design involving 25 second-semester English Education students. Data were collected through a 20-item Likert-scale questionnaire and semi-structured interviews. The quantitative findings showed mean scores ranging from M = 3.52 to M = 4.20, with 82% of responses categorized as positive (agree and strongly agree), indicating generally favorable perceptions. Students reported improvements in vocabulary, pronunciation, motivation, and speaking confidence. Interview results supported these findings, although challenges such as fast speech rate and unfamiliar vocabulary were identified. Overall, CNN news videos are perceived as effective authentic materials for supporting speaking development in EFL higher education contexts when accompanied by appropriate instructional guidance.